2012
DOI: 10.1002/j.0022-0337.2013.77.2.tb05457.x
|View full text |Cite
|
Sign up to set email alerts
|

Information‐Seeking Behaviors of Dental Practitioners in Three Practice‐Based Research Networks

Abstract: Research on the information-seeking behaviors of dental practitioners is scarce. Knowledge of dentists' informationseeking behaviors should advance the translational gap between clinical dental research and dental practice. A cross-sectional survey was conducted to examine the self-reported information-seeking behaviors of dentists in three dental practice-based research networks (PBRNs). A total of 950 dentists (65 percent response rate) completed the survey. Dental journals and continuing dental education (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 25 publications
(30 reference statements)
2
53
0
Order By: Relevance
“…With the growth of online access and resources, researchers have studied how, where, and why clinicians access both traditional and electronic resources [ 1 , 5 , 9 , 20 - 24 ]. These studies have laid the groundwork for understanding the relative attraction and use of online sources.…”
Section: Discussionmentioning
confidence: 99%
“…With the growth of online access and resources, researchers have studied how, where, and why clinicians access both traditional and electronic resources [ 1 , 5 , 9 , 20 - 24 ]. These studies have laid the groundwork for understanding the relative attraction and use of online sources.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in many countries have assessed professional and knowledge updating and information-seeking practices among dentists [ 9 , 10 , 13 16 ]. In these studies [ 9 , 10 , 13 16 ], factors such as a lack of clear answers to clinical questions, insufficient computer literacy, and exposure to studies reporting diverging outcomes were mentioned as barriers to accessing information and should be addressed to overcome the problems of transferring information into practice. Most of those studies also indicated a low reliance on evidence-based information resources during clinical practice, and that dentists’ experience plays a significant role in their updating patterns.…”
Section: Introductionmentioning
confidence: 99%
“…However, the 20% of clinicians who report going to the peer-reviewed literature first may not obtain much better information than Google searchers. Of the six articles published in dental journals noted earlier, only one appears in any of the journals that dentists have identified as among the publications they read regularly 35,36 . Even if these dentists then have access to and consult major publications in other disciplines -which is unlikely due to paywalls, the information contained would not be specific to oral health and thus the salience of that information for practicing dental professionals is questionable.…”
Section: Discussionmentioning
confidence: 97%